2015
DOI: 10.1586/17474086.2015.1024650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on the treatment of non-Hodgkin’s lymphoma: a systematic review

Abstract: Treating non-Hodgkin's lymphoma in patients with comorbidities can be challenging because of possible interactions that may alter the treatment efficacy. We conducted a systematic review to determine the impact of comorbidities on various outcomes, evaluate the current data, and provide recommendations for future research. Twenty-one articles were selected. However, the study populations and design were greatly heterogeneous, and the quality of reporting was generally weak. The majority of studies demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Overall, Terret et al . did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS [].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Overall, Terret et al . did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS [].…”
Section: Discussionmentioning
confidence: 85%
“…The majority of studies that have evaluated the prognostic influence of comorbidity in DLBCL have been nonpopulation‐based, limited in size (median n = 165, range 41–387 as reviewed by Terret et al . ), and restricted to an elderly population . Although the majority of these studies demonstrate an association between a high comorbidity index and inferior overall survival (OS), lower response rates or increased therapy‐related toxicities, some do not .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is unclear how geriatric syndrome contributes to outcomes. A systematic review has found that increasing numbers of comorbidities adversely affect survival in NHL (Terret et al, 2015). Similar studies have identified poor nutrition, low hemoglobin, and frailty as risk factors for early treatment withdrawal and poor outcome (Park et al, 2015; Aaldriks et al, 2015).…”
mentioning
confidence: 99%
“…Most precision medicine has focused on the biological features of the disease (as opposed to the patient) and on younger and generally healthier individuals who are offered entry into clinical trials. [118][119][120][121] There is growing awareness of the difference of results in clinical trials vs clinical practice (the efficacy-effectiveness gap 122 ), according to which there is comparatively little evidence on the optimal care of older and more comorbid patients. Although there are some published experiences with comorbidity scores and geriatric scales, 123,124 most of them are retrospective or observational, with little controlled evidence.…”
Section: Study Populationmentioning
confidence: 99%